The Political Costs of Austerity - Gabriel, Ricardo Duque; Klein, Mathias; Pessoa, Ana Sofia (The Review of Economics and Statistics, 2023)
Using a novel regional database covering over 200 elections in several European countries, this paper provides new empirical evidence on the political consequences of fiscal consolidations. To identify exogenous reductions in regional public spending, we use a Bartik-type instrument that combines regional sensitivities to changes in national government expenditures with narrative national consolidation episodes. Fiscal consolidations lead to a significant increase in extreme parties' vote share, lower voter turnout, and a rise in political fragmentation. We highlight the close relationship between detrimental economic developments and voters' support for extreme parties by showing that austerity induces severe economic costs through lowering GDP, employment, private investment, and wages. Austerity-driven recessions amplify the political costs of economic downturns considerably by increasing distrust in the political environment.